'Just be Brave' – The Experiences of Young Witnesses in Criminal Proceedings in Northern Ireland. (27th February 2013) - Hayes, David; Bunting, Lisa
<x xml:space="preserve">Abstract</x> The last three decades have witnessed considerable interest in the position of children and young people acting as witnesses in criminal cases and on how best to facilitate them to give their best evidence and minimise the trauma involved. This paper presents the findings of a small‐scale study in Northern Ireland examining the experiences of young witnesses pre‐trial, during the trial and post‐trial. Interviews were carried out with 37 young witnesses and 33 parents, and a questionnaire was completed by 16 volunteers and practitioners working in a local young witness support scheme. The findings indicate that the prospect and actuality of giving evidence in a criminal trial are anxiety‐provoking and stressful for the majority of young witnesses. Particular issues identified are delay, both in terms of cases coming to court and in waiting times at court, the availability of pre‐trial preparation and support, facilities at court buildings and the treatment of young people during cross‐examination by defence lawyers. The paper concludes that there is a continuing need to strive for improvement, and that this necessarily involves reviewing the experiences of young witnesses and seeking their views on measures designed to enable them to give their best evidence. Copyright © 2013 John Wiley & Sons, Ltd. <boxed-text content-type="pullQuote" id="car2242-blk-0001" position="anchor" orientation="portrait"> 'A small‐scale study in Northern Ireland examining the experiences of young witnesses pre‐trial, during the trial and post‐trial' </boxed-text> Key Practitioner Messages Acting as a witness is a stressful experience for children and, for some, distress can persist post‐trial regardless of the trial outcome. Delay, both in cases coming to court and waiting times at court, is a significant issue which exacerbates the stress experienced by young witnesses. Pre‐trial support is highly valued but referrals to witness support schemes need to be made in a timely manner to ensure that young witnesses are appropriately assessed and supported. <boxed-text content-type="pullQuote" id="car2242-blk-0002" position="anchor" orientation="portrait"> 'A significant issue which exacerbates the stress experienced by young witnesses' </boxed-text>